The Thermal Performance of Traditional Residential Buildings in Kathmandu Valley - Bajracharya, Sushil B. (Journal of the Institute of Engineering, 2014)
This paper seeks to investigate into the aspects of thermal performance of traditional residential buildings in traditional settlements of Kathmandu valley. This study proceeds to analyze the detailed field data collected, with a view to identify the indoor thermal environment with respect to outdoor thermal environment in different seasons. This paper also compares the thermal performance of traditional buildings with modern residential buildings of traditional settlements of the valley. There is a regression analysis to obtain information about the thermal environment of different traditional and modern residential buildings with different conditions. The paper concludes that, thermal performance of traditional residential building, adapted in various ways to the changing thermal regime for thermal comfort is better than that of contemporary buildings. DOI: http://dx.doi.org/10.3126/jie.v10i1.10898 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 172–183